Devote: a decentralised, electronic voting platform - Chua, Matthew Wei Cheng (Nanyang Technological University, 2024)
deVOTE is a trustless and decentralised online electronic voting system, that allows eligible users to vote for specific candidates or proposals confidentially. It is built on a decentralised, public blockchain that utilises Fully Homomorphic Encryption (FHE), to enable private, yet transparent transactions. Current features include authenticated voting, specified voting periods, as well as the option to allow or disallow the casting of void votes. A full working demonstration is currently deployed on the Zama Devnet, an Ethereum Virtual Machine blockchain.